2018
DOI: 10.1093/qjmed/hcy162
|View full text |Cite
|
Sign up to set email alerts
|

Skipping breakfast and the risk of coronary artery disease

Abstract: Habitual breakfast skippers are at increased risk for development of CAD and hypertension in Western India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 20 publications
2
9
1
3
Order By: Relevance
“…Breakfast skippers are associated with a higher body mass indices and higher levels of hemoglobin A1C (HbA1C), another marker for glucose metabolism dysfunction), leading to an increased risk of obesity and diabetes [ 103 , 104 ]. They also present elevated blood pressure and increased levels of LDL which indicate a higher risk for CVD [ 105 , 106 ].…”
Section: Modern Lifestyle and Circadian Disruption: Leaving The Door Open To Metabolic Diseasesmentioning
confidence: 99%
“…Breakfast skippers are associated with a higher body mass indices and higher levels of hemoglobin A1C (HbA1C), another marker for glucose metabolism dysfunction), leading to an increased risk of obesity and diabetes [ 103 , 104 ]. They also present elevated blood pressure and increased levels of LDL which indicate a higher risk for CVD [ 105 , 106 ].…”
Section: Modern Lifestyle and Circadian Disruption: Leaving The Door Open To Metabolic Diseasesmentioning
confidence: 99%
“…To the best of our knowledge, age, hypertension, diabetes, dyslipidemia, overweight, and coronary calcification are risk factors of CAD. [11][12][13] Suk et al 14 showed that the amount of PAT was associated with some risk factors of cardiovascular diseases. In the Framingham Heart Study, BMI was significantly associated with PAT volume.…”
Section: Discussionmentioning
confidence: 99%
“…高血糖增加 血红蛋白糖基化, 其在心肌组织中的沉积导致纤维化 降低心肌收缩力和顺应性, 促进冠心病的发生 [20] . 此 外, 不吃早餐 [21] 、饮酒 [22] 、高尿酸 [23] 、高同型半胱氨 酸 [24] 等多个因素也显著增加冠心病风险. 有规律的、 中等至剧烈的体育运动有助于控制血液胆固醇水平、 高血压、糖尿病和肥胖等多个冠心病危险因素, 降低 冠心病及其他心血管疾病风险 [25,26] .…”
Section: 不可控因素unclassified